p53 functional states are associated with distinct aldehyde dehydrogenase transcriptomic signatures - Gui, Shanying (Sci Rep, 2020)
p53 and aldehyde dehydrogenase (ALDH) have been implicated in key tumorigenesis processes including cancer initiating cell (CIC) maintenance; however, the relationship between these two mediators remains poorly defined. In this study, ALDH isoform expression diversity was revealed in CICs with disparate p53 functional states: gain of function, high risk p53 mutation (p53HRmut) and wildtype p53 (p53WT) inactivated by the human papillomavirus 16 (HPV16) E6 oncogene. Interrogation of head and neck squamous cell carcinoma (HNSCC) cell lines and patient tumors showed that HPV16+/p53WT cases have higher ALDH variance score (AVS), a measure of tumor ALDH isoform expression diversity, compared to HPV−/p53HRmut cases (p = 0.03). AVS and several individual ALDH isoforms were associated with prognosis in HPV16+/p53WT HNSCC but not in HPV−/p53HRmut HNSCC. Knockdown of the dominant ALDH isoform in high AVS HNSCC depleted the CIC pool in vitro and in vivo. Our results demonstrate that p53 functional states are associated with distinct ALDH isoform transcriptomic signatures. Moreover, tumor ALDH profiling may provide insight on which ALDH isoform to target in high AVS HNSCC tumors to deplete the CIC population.